The changing face of imperialism
1 online resource (xiv, 256 pages)
Keywords: "This volume reiterates the relevance of imperialism in the present, as a continuous arrangement, from the early years of empire-colonies to the prevailing pattern of expropriation across the globe. While imperialism as an arrangement of exploitation has sustained over ages, measures deployed to achieve the goals have gone through variations, depending on the network of the prevailing power structure. Providing a historical as well as a conceptual account of imperialism in its 'classical' context, this collection brings to the fore an underlying unity which runs across the diverse pattern of imperialist order over time. Dealing with theory, the past and the contemporary, the study concludes by delving into the current conjuncture in countries including Latin America, the United States and Asia. The Changing Face of Imperialism will provide fresh ideas for future research into the shifting patterns of expropriation--spanning the early years of sea-borne plunder and the empire-colonies of nineteenth-century to contemporary capitalism, which is rooted in neoliberalism, globalization and free market ideology. With contributions from major experts in the field, this book will be a significant intervention. It will be of interest to scholars and researchers of economics, politics, sociology and history, especially those dealing with imperial history and colonialism. "--Provided by publisher.